Preparation, structure characterization and functional properties of pea dregs resistant dextrin - Li, Liangyu; He, Tianfeng; Ling, Yang; Li, Xiaohong; Sui, Chunguang; Cao, Rong-an; Li, Chaoyang (Frontiers in Sustainable Food Systems, 2023)
In the present study, the preparation and simulated moving bed chromatographic purification process conditions of pea-resistant dextrin were optimized using pea production waste-pea residue as raw material, and structural characterization and functional properties of pea residue-resistant dextrin were analyzed. The results showed that the optimal preparation process conditions for pea-resistant dextrin were as follows: acid concentration 1.0%, acid addition 7.3%, treatment temperature 178.8 ℃, and treatment time 92.5 min. Subsequently, the pea-resistant dextrin content of 42.15±0.16% was obtained. The optimal SSMB purification conditions were as follows: feed volume 455 g/h, feed volume 682 g/h, circulation volume 346 mL, outlet concentration 24.8±0.2%, purity 99.35±0.17%, and yield 91.08±0.42%. The structural characterization revealed that pea-resistant dextrin had large and variable particle size and amorphous structure; the chemical bond or functional group differences between pea-resistant dextrin and pea starch were not significant; pea-resistant dextrin was a glucose-based dextran with a monosaccharide composition of 2.6% arabinose, 1.5% xylose, and 95.9% glucose, and its molecular weight was (601.1±8.5)×103 u. Functional characterization revealed that the RS content of pea-resistant dextrin was 92.35%, which had significantly slow digestive properties as well as hypoglycemic and hypolipidemic effects.